Study on the Mechanism of Central Venous Needle Injection - ZHANG Yong-de; DAI Xue-song; ZHANG Guan-yi; JIANG Jin-gang (Journal of Harbin University of Science and Technology, 2021)
The characteristics of puncture force in different soft tissues me different. The establishment ofpuncture force model for soft tissue can provide theoretical basis for the position prediction of punctme needle in the process of puncture, improve the accuracy of puncture and improve the treatment effect. In this paper, the central venipuncture is analyzed, the puncture process is divided into four stages, and the force of each stage is modeled. The mechanical model of puncture needle in the process of puncture was verified, and the single factor influencing the puncture force was studied. The experimental results show that the puncture force increases with the increase of the puncture angle, the puncture force increases with the increase of the diameter of the puncture needle, and the puncture speed has little influence on the puncture force.